Frenectomy with Lateral Pedicle Flap: A Novel Surgical Approach for Maintaining The width of Attached Gingiva: A Case Report - Naina Pattnaik; Ruchi Arora; Rinkee Mohanty; Anurag Satpathy; Bikash Nayak (Indian Journal of Forensic Medicine & Toxicology, 2021)
The aberrant frenum is usually managed by a common periodontal plastic surgical procedure called frenectomyto create a zone of attached gingiva. This surgical approach may often lead to loss of interdental papillacreating unacceptable esthetic results in the maxillary incisor region. Thus this case reported frenectomycombined with a laterally positioned flap which was a better approach to achieve primary closure. Andthe lateral pedicle sutured in midline provided better and faster healing with excellent esthetic results. Theesthetic results were far more superior then the classical frenectomy technique with a considerable gain inattached gingiva.